Mapping the landscape of digital financial inclusion and proposing integrative framework: trends, influential works, and future directions - Vaishali Kamboj; Dipasha Sharma (Humanities & Social Sciences Communications)
Abstract This study presents a comprehensive review aimed at elucidating the performance and intellectual framework of digital financial inclusion (DFI) research. A bibliometric analysis was performed on 311 research articles sourced from the Scopus database up to 2023. The study identifies influential articles, prominent journals, and leading authors, institutions, and countries within this field. Furthermore, it explores nine key themes in DFI research, contributing to the advancement of the field. An integrative framework is proposed, highlighting future research opportunities across DFI domains and suggesting policy implications to enhance DFI globally, particularly in underserved countries.